Expanding the solid-state landscape of dexamethasone: a specific sandwich structure in facilitating the formation of kinetically stable cocrystals from mechanochemistry. Issue 33 (27th July 2022) - Wong, Si Nga; Low, Kam-Hung; Weng, Jingwen; Chan, Ho Wan; Chow, Shing Fung
Abstract : We herein report the successful synthesis of the first two dexamethasone cocrystals from mechanochemistry. Abstract : Dexamethasone (DEX), a widely prescribed anti-inflammatory drug, displays limited crystal forms. Cocrystallization constitutes an untapped strategy for expanding its solid-state landscape with improved pharmaceutical properties, yet no dexamethasone cocrystal has been discovered. Herein, we report for the first time the successful synthesis of two DEX cocrystals with benzenediols (catechol and resorcinol) via mechanical treatment.